2017
DOI: 10.1002/slct.201700381
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Preparation of Polyethylene Glycol/ Silver Nanoparticles Composite Phase Change Materials with Enhanced Thermal Conductivity

Abstract: Phase change materials (PCMs) have been widely used as efficient materials in latent heat thermal storage systems for various applications. The poor thermal conductivity of most organic PCMs, however, has long been considered as one of big obstacles hindering their practical applications. Here, we report the first example of in situ reduction of AgNO3 precursor by PEG for preparation of polyethylene glycol/silver nanoparticles (PEG/Ag) PCMs nanocomposites with enhanced thermal conductivity only though a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…To counteract this, additives with high thermal conductivity such as carbon black or silver nanoparticles can be added. [48][49][50][51] The same behavior can also be observed using DSC (see ESI 4).…”
Section: Resultssupporting
confidence: 70%
“…To counteract this, additives with high thermal conductivity such as carbon black or silver nanoparticles can be added. [48][49][50][51] The same behavior can also be observed using DSC (see ESI 4).…”
Section: Resultssupporting
confidence: 70%
“…PEG is also known as a reducing agent for the formation of silver nanoparticles. 17,18 Silver has a low tendency of ionization compared to other metals. In other words, silver ions have strong oxidizing power to be reduced to metallic silver.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The low mass fraction-addition of metal oxide nanoparticles (MONPs), copper oxide (CuO), aluminum oxide (Al 2 O 3 ), zinc oxide­(ZnO), tin oxide (SnO 2 ), zirconium dioxide (ZrO 2 ), titanium dioxide (TiO 2 ), ferric oxide (Fe 2 O 3 ), and silicon oxide (SiO 2 ), can significantly enhance the thermal conductivity of various organic PCMs. However, the studies about the use of MONPs as an additive agent to improve thermal conductivity of PEGs are limited to a few studies. Liang et al have prepared PEG/silver nanocomposite and reported the thermal conductivity enhancement rate as 211% for a mass fraction of 4:1 to 1:1 (PEG to AgNO 3 ). Babapoor et al fabricated PEG1000/polyamide composite including various MONPs (SiO 2 , Al 2 O 3 , Fe 2 O 3 , and ZnO) as supporting material.…”
Section: Introductionmentioning
confidence: 99%